1998
DOI: 10.1128/jb.180.18.4856-4864.1998
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Response and Characterization of theoxyR-ahpCandfurA-katGLoci inMycobacterium marinum

Abstract: Oxidative stress response in pathogenic mycobacteria is believed to be of significance for host-pathogen interactions at various stages of infection. It also plays a role in determining the intrinsic susceptibility to isoniazid in mycobacterial species. In this work, we characterized the oxyR-ahpC and furA-katG loci in the nontuberculous pathogen Mycobacterium marinum. In contrast to Mycobacterium smegmatis and likeMycobacterium tuberculosis and Mycobacterium leprae, M. marinum was shown to possess a closely l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…However, some studies showed that the susceptibility to H 2 O 2 was not determined by katG gene [5,15]. For example, Western blotting analysis demonstrated that the AhpC protein of Mycobacterium marinum was increased after H 2 O 2 treatment [25] which appeared to be independent from the katG mediated H 2 O 2 resistance [25]. More importantly, the Southern Indian [7] and our Western mutant (sigJ knockout) strains of M. tuberculosis contain KatG but are sensitive to killing by H 2 O 2 [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies showed that the susceptibility to H 2 O 2 was not determined by katG gene [5,15]. For example, Western blotting analysis demonstrated that the AhpC protein of Mycobacterium marinum was increased after H 2 O 2 treatment [25] which appeared to be independent from the katG mediated H 2 O 2 resistance [25]. More importantly, the Southern Indian [7] and our Western mutant (sigJ knockout) strains of M. tuberculosis contain KatG but are sensitive to killing by H 2 O 2 [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…The katG encodes a Catalase-Peroxidase which is important for the virulence of M. tuberculosis (36). The katG locus is genetically linked to furA, which encodes a homolog of the ferric uptake regulator (37). Among all the mycobacterial species studied, the DNA region immediately upstream of the katG genes is highly conserved and encodes furA, suggesting a putative involvement of the FurA protein in katG regulation.…”
Section: Antioxidant Defense In Mycobacteriamentioning
confidence: 99%
“…The fur-like genes have also been reported to be catalase-peroxidase regulators in Streptomyces (Zou et al, 1999;Hahn et al, 2000). In some Mycobacterium species that are naturally mutated at OxyR, fur homologue has been proved as the regulator of the katG gene encoding catalase-peroxidase for the response to oxidative stress (Pagan-Ramos et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The primary role for catalases is to protect cells against the damage caused by reactive oxygen species to cellular components, including nucleic acids, proteins and cell membranes (Imlay and Linn, 1988;Storz and Imlay, 1999). Catalases have been implicated to be important for the survival of some pathogenic bacteria during infection (Loprasert et al, 1996;Laochumroonvorapong et al, 1997;Pagan-Ramos et al, 1998) and even for the life span of a multicellular organism (Melov et al, 2000). The catalases present in different bacteria are diverse in protein structures, cofactor requirements and gene regulations (Bravo et al, 1997;Loewen, 1997).…”
Section: Introductionmentioning
confidence: 99%